Autocontrole e impulsividade: um estudo do efeito de atraso de pontos e do atraso de troca em crianças - Martins, Luciana Júlio (2009)
The present study has been carried out with the objective of examining the effects of the exchange of conditioned reinforcement (tokens) with the final reinforcement (gifts), on children, by manipulating the delay of points and of exchange in choices between a delayed reinforcement of higher value (self-control) and an immediate reinforcement of lower value (impulsiveness). Such choices have been regularly presented in experimental studies of self-control. This study has been performed in seven children with ages between 8 and 10, who have been submitted to a concurrent-chain schedule with 3 periods in a notebook. In the first period, called period of choice, a VI10-VI10 was programmed to each of the two components presented on the computer screen. The choice of one of them produced, as a consequence, the period of delay of the reinforcement (FT), characterized by the screen becoming black. After that, a new period started in which the acquisition of tokens was possible. All the participants have been submitted to four different experimental conditions. The first two consisted in evaluating the control of dimensions such as delay and magnitude of the reinforcement over the action of responding and were called correspondently evaluation of sensitivity to the delay of the reinforcement and evaluation of sensitivity to the magnitude of the reinforcement. The other two conditions were called point-delay and exchangedelay. The point-delay condition consisted of submitting the participants to three values of delay (30 , 75 e 120 ) between the emission of a response in the period of choice (VI10-VI10) and the period of acquisition of the conditioned reinforcement (tokens which presented on the computer screen). At the end of each experimental session he screen showed the number of tokens received e these tokens were exchanged for the final reinforcement (gifts). The condition of exchange-delay, consisted of submitting the participants to three values of delay (1,7 and 14 days) to perform the exchange the conditioned reinforcement for the gifts. The period of delay after the period of choice was always 1 second in this condition and the tokens were made available after this delay. However, the exchange for the final reinforcements was only performed on the days determined by the contingency in operation, not at the end of the session as in the point-delay condition. The results showed that all the participants were sensitive to the dimensions delay and magnitude of the reinforcement in the evaluation of their sensitivity to them. Considering the conditions of delay of scoring and exchange delay, four amoung the seven participants preferred the alternative of self-control and three preferred the alternative of impulsiveness, in both conditions. Hence, the effect of the variable exchange-delay was not observed to be different from the effect of point-delay on the participants response